Pengaruh Campuran Tepung Jagung dan Kacang Tanah Terhadap Daya Terima dan Sifat Kimia Food Bar Sebagai Pangan Darurat - Arizkha Raudiyami Putri; Erwandi (Poltekkes Kemenkes Aceh, 2024)
Emergency food has good acceptability, high nutritional content, is easy to distribute, is practical to consume and has a long shelf life. Food bars can be used as an emergency food product because they have these requirements. Corn flour and peanuts are local foods that have many sources of nutrients so they can be used in making food bars. This research aims to determine the effect of a mixture of corn flour and peanuts on the acceptability and chemical properties of food bars as emergency food. The research was carried out in November 2023 - February 2024. The research design is an experiment using a non-factorial Completely Randomized Design (CRD). Food bar formulation with a mixture of 120 gr, 100 gr, and 80 gr corn flour while 80 gr, 100 gr, and 120 gr peanuts. Organoleptic test and chemical test data were analyzed using the ANOVA test and Duncan's advanced test. Analysis of the selected food bar from test results by semi-trained panelists is F1 with a mixture of 120 grams of corn flour and 80 grams of peanuts. The mixture of corn flour and peanuts had no significant effect on color (p value 0.938), aroma (p value 0.944), taste (p value 0.944), texture (p value 0.976), and ash content (p value 0.435). However, it had a significant effect on water content (p value 0.000), protein content (p value 0.001), fat content (p value 0.012), and carbohydrate content (p value 0.015). The results of the chemical test analysis showed a water content of 27.94%, ash content of 1.13%, protein content of 12.29%, fat content of 9.41%, and carbohydrate content of 55.71%.